UNDERSTANDING THE SCIENCE OF GLOBAL WARMING AND ITS HEALTH IMPACTS: QUALITATIVE STUDY - Sri Mulyono; Putri Maha Dewi, Sumarwoto, Herwin Sulistyowati; Imam Hanafi (ADISAM Publisher, 2023)
Due to its potential effects on health, global warming is a pressing environmental problem that has received much attention recently. This qualitative study aims to get experts' perspectives on the science behind global warming and its effects on health. Ten experts in climate change, public health, and environmental science participated in semi-structured interviews to gather the data. A thematic approach was used to analyze the data, which involved coding the data for themes and sub-themes. The examination uncovered that a worldwide temperature alteration is fundamentally brought about by human exercises, especially the outflow of ozone-depleting substances. The effects of a dangerous atmospheric deviation include an expanded commonness of respiratory infections, cardiovascular sicknesses, heat-related diseases, and emotional well-being issues. Additionally, the experts emphasized the disproportionate impact of global warming on vulnerable populations, such as low- income communities, indigenous groups, and developing nations. To relieve the impacts of a worldwide temperature alteration, the specialists recommended a few procedures, including decreasing ozone-depleting substance outflows, advancing energy productivity and environmentally friendly power, executing a green framework, and expanding public mindfulness and training. However, they also acknowledged the difficulties of implementing these strategies, especially in the face of political and economic obstacles. In general, this study offers valuable insights into the science of global warming and the effects it has on health. According to the findings, immediate action is required to address the effects of global warming on health, particularly in vulnerable populations. The study emphasizes the significance of interdisciplinary collaborations and the necessity for policymakers to place public health at the forefront of strategies for reducing the effects of climate change and adapting to it.